2022
DOI: 10.3390/encyclopedia2040122
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-Associated Encephalopathy (COVEP): Basic Aspects of Neuropathology

Abstract: SARS-CoV-2, a member of the betacoronavirus group and causative agent of COVID-19, is a virus affecting multiple systems, not only the respiratory. One of the systems affected by the virus is the central nervous system, with neuropathological studies reporting a wide set of morphological phenomena—neuroinflammation, vascular and blood-brain barrier alterations, neurodegeneration, and accelerated aging, while contradicting data is present on the direct neuroinvasive potential of the virus and active viral repli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 186 publications
(325 reference statements)
0
5
0
Order By: Relevance
“…The first of the disputed properties of the virus when it comes to the CNS is that of neuroinvasiveness -the ability of the infectious agent to enter the nervous system; by itself, this mechanism does not always lead to pathological changes such as neurovirulence, with and without the possibility of changes in homeostasis (21,27,28). Multiple studies have reported different results regarding detecting viral particles within the CNS, with varying analysis methods (29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The first of the disputed properties of the virus when it comes to the CNS is that of neuroinvasiveness -the ability of the infectious agent to enter the nervous system; by itself, this mechanism does not always lead to pathological changes such as neurovirulence, with and without the possibility of changes in homeostasis (21,27,28). Multiple studies have reported different results regarding detecting viral particles within the CNS, with varying analysis methods (29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…Biomed Rev 34, 2023 COVID-19 and the hippocampus the native inflammatory cells can damage the neurons rather than the viral agent itself (21,27,37).…”
Section: Figure 5 Angiocentric Early Skip-lesion Hande Stain Original...mentioning
confidence: 99%
See 3 more Smart Citations